Йовалег: роман-дилогия / Генрих Перевощиков - Перевощиков Генрих Ксенофонтович (Удмуртия, 1988)
Экземпляры: Аб (20221019) / Инвентарный номер: 118769 / Цена: 10.00 / Авт.знак: П 27 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)